River Regulation Causes Rapid Changes in Relationships Between Floodplain Oak Growth and Environmental Variables - Netsvetov, Maksym; Prokopuk, Yulia; Puchałka, Radosław; Koprowski, Marcin; Klisz, Marcin; Romenskyy, Maksym (Frontiers in Plant Science, 2019)
The radial growth of pedunculate oak (Quercus robur), a species often ecologically dominating European deciduous forests, is closely tied up with local environmental variables. The oak tree-ring series usually contain a climatic and hydrologic signal that allows assessing the main drivers of tree growth in various ecosystems. Understanding the climate-growth relationship patterns in floodplains is important for providing insights into the species persistence and longevity in vulnerable riverine ecosystems experiencing human-induced hydrology alteration. Here, we use a more than 130 years long instrumental records of local temperature, precipitation, and water levels in the Dnipro River in Kyiv to demonstrate that the implementation of river regulation has impeded the established relationship between the radial growth of floodplain oak and local hydro-climatic conditions. Before the river flow has been altered by engineering modifications of 1965-1977, the water level in the Dnipro River was the key driver of oak radial growth, as reflected in the tree-ring width and earlywood width. Upon river regulation the positive effect of water level on oak growth diminished and subsequently reversed to negative, resulting from a seasonal groundwater surplus. The decrease in the correlation between oak growth indices and the river’s water level in April-June was unprecedentedly rapid and clearly distinguishable among other changes in the growth-to-climate relationship. Our findings further demonstrate that trees growing in areas exposed to urban development are the most susceptible to downside effects of river regulation.